Female-instigated divorce (Khula)and Debate over Triple Talaq (Divorce) in Muslim Society - Ahmed, AbdusSagir (International Journal of Psychosocial Rehabilitation, 2020)
Women are half of the society. Women‟s contributions to the society is no less than that of the men. But women have been being deprived of their legitimate rights in every aspect of the society since time immemorial. Women cannot enjoy the rights as the men can enjoy. Besides, women have been victim of many injustice. One among them is that Muslim women keep being subject to divorce at any point of time due to practice of triple Talaq. It is pertinent to mention here that the relationship between men and women is deemed to be divine. They build their marital relationship according to religious rules and also break up accordingly. Breaking up of the relationship in standard language can be called „Divorce‟ and the rules for divorce vary from religion to religion. For instance, women have no right to divorce in many of the religions. On one hand, Islam has granted men and women right to divorce alike. Muslims practice many forms of Talaqs. One of the Talaqs Muslims practice isTalaq-e-biddat or instant triple Talaq. It has created a lot of controversy in the Muslim society, particularly in Indian Muslim society i.e. mostly it‟s practiced by Indian Muslims. It is noticed that triple Talaq results in the severe suffering of women. Practice of triple Talaq is also a violation of Quranic rules. The objectives of this paper is to discuss the Muslim women‟s right to divorce and ongoing Debate over Triple Talaq (Divorce) in Indian Muslim Society in the light of Islamic texts. The discussion will be based on the Quran and authentic prophetic traditions.